(untitled) (FUDMA JOURNAL OF SCIENCES, 2023)
The study is aimed at validating antibacterial claims of some herbal products sold in Otukpo, Benue State. The test organisms include: Staphylococcus aureus, Salmonella typhi, Escherichia coli, and Proteus vulgaris, which were obtained from Medical Laboratory unit of General Hospital Otukpo and were confirmed by sub-culturing on appropriate selective media and the use of biochemical tests in the Microbiology Laboratory, Department of Science Laboratory, Benue State Polytechnic, Ugbokolo. Ciprofloxacin was used as a positive and negative control. The degree of susceptibility of the test isolates to each herbal product was determined by measuring the diameter of the zones of inhibition. Product Code I had the highest zone of inhibition of 36 mm against Escherichia coli, followed by Product Code F with zone of inhibition of 32 mm, while the least sensitive against Escherichia coli was Product Code D with zone of inhibition of 17 mm; all the herbal products where resistant to Staphylococcus aureus. Against Escherichia coli, the MIC and MBC values for Product Code F were 75 mg/ml and 100 mg/ml, respectively; while for Salmonella typhi, the MIC and MBC values for Product Code G were 28 mg/ml and 70 mg/ml, respectively. The overall result showed that most of the antibacterial claims by the herbal producers were not true as validated in this present work